Prevalence of Carotid Plaque in a 63‐ to 65‐Year‐Old Norwegian Cohort From the General Population: The <styled-content style="fixed-case">ACE</styled-content> (Akershus Cardiac Examination) 1950 Study - Håkon Ihle‐Hansen (Wiley, 2018)
BackgroundNew data on extracranial carotid atherosclerosis are needed, as improved ultrasound techniques may detect more atherosclerosis, the definition of plaque has changed over the years, and better cardiovascular risk control in the population may have changed patterns of carotid arterial wall disease and actual prevalence of established cardiovascular disease. We investigated the prevalence of atherosclerotic carotid plaques and carotid intima–media thickness (cIMT) and their relation to cardiovascular risk factors in a middle‐aged cohort from the general population. Methods and ResultsWe performed carotid ultrasound in 3683 participants who were born in 1950 and included in a population‐based Norwegian study. Carotid plaque and cIMT were assessed according to the Mannheim Carotid Intima–Media Thickness and Plaque Consensus, and a carotid plaque score was used to calculate atherosclerotic burden. The participants were aged 63 to 65 years, and 49% were women. The prevalence of established cardiovascular disease was low (10%), but 62% had hypertension, 53% had hypercholesterolemia, 11% had diabetes mellitus, and 23% were obese. Mean cIMT was 0.73±0.11 mm, and atherosclerotic carotid plaques were present in 87% of the participants (median plaque score: 2; interquartile range: 3). Most of the cardiovascular risk factors, with the exception of diabetes mellitus, obesity and waist–hip ratio, were independently associated with the plaque score. In contrast, only sex, hypertension, obesity, current smoking, and cerebrovascular disease were associated with cIMT. ConclusionsWe found very high prevalence of carotid plaque in this middle‐aged population, and our data support a greater association between cardiovascular risk factors and plaque burden, compared with cIMT. Clinical Trial RegistrationURL: https://www.clinicaltrials.gov. Unique identifier: NCT01555411.